Intramuscular myxoma of the longus colli mistaken for a cervical rootlet schwannoma. Issue 2 (4th February 2021) - Mijalis, Eleni Marie; Manzi, Brian; Cuellar, Hugo; Nathan, Cherie Ann O
Abstract : An 86-year-old woman was referred to the otolaryngology clinic for a 1-year history of a painless, slow-growing neck mass. Physical examination showed a fixed, immobile right level II neck mass with normal vocal cord movement. MRI demonstrated a lobulated mass laterally displacing the carotid vessels, consistent with a schwannoma. Despite the pathognomonic radiographic findings for schwannoma, core needle biopsy of the mass was consistent with intramuscular myxoma (IM), which rarely presents in the head and neck region. After multiple years of slow growth with bulging into the pharynx, the patient ultimately underwent surgery to reduce the risk of airway compromise. The location of this IM together with its unusual imaging appearance is a unique finding in the head and neck and adds to the differential diagnoses for neck masses displacing the carotid sheath.